(untitled) (Annals of Medical Research, 2021)
Aim: A retrospective study was performed to determine of aeroallergens sensitivity in children.Material and Methods: Medical records of patients aged 1-16 years who presented at the Paediatric Allergy Polyclinic of Kahramanmaraş Children’s Hospital between August 2015 and July 2016. A 10-item allergy test was applied to patients. These tests were positive control (histamine), negative control (saline), grass, weed, house dust mite mixture, peanut, cockroach, alternaria, aspergillus, and cat epithelium and dog hair. The patients were separated into 3 groups as asthma, allergic rhinitis and asthma and allergic rhinitis combined.Results: A total of 1078 patients were administered the allergy tests. A positive result in the allergy skin test was determined in 311 patients. The male/female ratio was 199/112 (64%/36%) in the positive allergy test. Allergic rhinitis was determined in 144 (46.3%). The mean age of the patients was 6.6 ± 3.51 years in the asthma group, 10 ± 3.81 years in the allergic rhinitis group and 9.3 ± 3.89 years in the asthma +allergic rhinitis group. Grass pollen was the most frequently determined aeroallergen in all the patient and age groups. In the pre-school age group, the patients diagnosed with asthma were determined with the most aeroallergen sensitivity. In the patients diagnosed with both asthma and allergic rhinitis, house dust mite mixture was the 2nd most frequently determined aeroallergen in both pre-school and school-age children.Conclusion: In the region of Kahramanmaraş, it was significant that the most commonly determined aeroallergen was mixture 5 grasses in our study.